Phylogenetic Relationships of Ornamental Chaetodontidae in The South Coastal of West Java, Indonesia - Silma Safira Ihya; Agus Nuryanto; Romanus Edy Prabowo; Dian Bhagawati; Kusbiyanto Kusbiyanto (Jurnal Biodjati, 2020)
Marine ornamental trade has been developing for several years with Indonesia as one of the major exporter countries. Among the popular marine ornamental fish in the local and international markets belong to the family of Chaetodontidae. The existence of this family has been reported from several areas in Indonesia. However, no information is available in terms of their phylogenetic relationships of the fish from the south coast of West Java. The aim of this research was to asses the phylogenetic relationships among ornamental fish members of Chaetodontidae in the South Coast of West Java. Fish samples were collected from two trading sites Ujung Genteng and Taman Manalusu. Collected fish were identified using a previously published study. The evolutionary relationships among species were analyzed statistically through phylogenetic analysis based on maximum parsimony algorithm and Kimura 2- Parameter substitution model as implemented in PAUP 4.0 software. Tree branching pattern supported by 1000 bootstraps pseudo-replicates and out-group comparison. Daschyllus trimaculatus used as outgroup species. Based on the study, Chaetodontidae from the South Coast of West Java formed one monophyletic group compared to Dascylus trimaculatus with Chelmon rostratus was the basal species. All the remaining species were the derived species. There are CI and RI value gained. The consistency index (CI) value of this family is 0.5833, and the retention index (RI) is 0.5082.